PEMAHAMAN GURU TK NEGERI PEMBINA 1 MEDAN TERHADAP PEMBELAJARAN MENDALAM (DEEP LEARNING) - Adinda Tri Utami; Wan Nova Listia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze teachers' understanding of mindful learning, meaningful learning, and enjoyable learning. This study used a qualitative approach with 10 teachers as subjects. Data were collected through open-ended questionnaires and documentation in the form of open modules. Data analysis was conducted using descriptive qualitative techniques through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that teachers have varying degrees of understanding of these three learning concepts. In mindful learning, teachers understand aspects of awareness, attention, and emotional management, but have not yet outlined specific learning techniques. In meaningful learning, teachers have linked learning material to students' daily experiences, but have not yet explained them in depth and systematically. In enjoyable learning, some teachers understand learning as a fun process that actively engages students, while others still interpret it in a general way. Documentation shows that these three approaches have been discontinued in the learning process. Thus, teachers' understanding has been established, but still requires conceptual strengthening and improved implementation for optimal results.